2017
DOI: 10.19030/ajee.v8i2.10070
|View full text |Cite
|
Sign up to set email alerts
|

Women In Engineering: Insight Into Why Some Engineering Departments Have More Success In Recruiting And Graduating Women

Abstract: Universities across the United States (U.S.) are perplexed as to why fewer women than men study engineering and why even fewer complete the curriculum and earn an undergraduate degree in engineering. The percentage of undergraduate engineering degrees awarded annually to women in the U.S. since 2000 has remained relatively constant at around 20%. However, some engineering disciplines have had much greater success in graduating women, with some programs awarding 50% or more of their bachelor’s degrees to women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As Faulkner (2009) admitted, future studies definitely need to recruit more women to promote a more integrated socio-technical understanding of engineering and support more inclusive disciplinary membership. For example, as women show a greater interest in solving societal issues (Shealy et al, 2016), engineering departments can tactically attract and retain more women in engineering by providing specific real-life examples of how an engineering discipline benefits society (Bossart & Bharti, 2017). Creating a female-friendly curriculum and environment would also be helpful to attract more women into engineering programs, such as problem-based learning and technical skill-based assessment methods (Du & Kolmos, 2009).…”
Section: Gender and Ethnicity Issuesmentioning
confidence: 99%
“…As Faulkner (2009) admitted, future studies definitely need to recruit more women to promote a more integrated socio-technical understanding of engineering and support more inclusive disciplinary membership. For example, as women show a greater interest in solving societal issues (Shealy et al, 2016), engineering departments can tactically attract and retain more women in engineering by providing specific real-life examples of how an engineering discipline benefits society (Bossart & Bharti, 2017). Creating a female-friendly curriculum and environment would also be helpful to attract more women into engineering programs, such as problem-based learning and technical skill-based assessment methods (Du & Kolmos, 2009).…”
Section: Gender and Ethnicity Issuesmentioning
confidence: 99%
“…There are various factors for this under representation. Such as studies by [2], [8], [21], [14] [13], [25] found high school educational background, family education and lack of role models have an impact on decision to study engineering and technology. Studies [16], [19], [17], [24]; [6], [22], [23], [26]found that employment participation of women engineering and technology is low and is male dominated sector.…”
Section: Introductionmentioning
confidence: 99%
“…Although overall the university enrolls more undergraduate women [9], this is not true for the college of engineering. As reported in 2016 only 24% of undergraduates and graduates seeking engineering degrees at this university were women [10].…”
Section: Introductionmentioning
confidence: 75%
“…Interest was a major driving force for these women to choose engineering; future research may look at what sparks an interest in engineering, and how this interest is sustained. As previous research has shown, this may involve seeing engineering as a way to make a difference in the lives of others/improving society [10], [39], [28] as well as addressing the desire for a successful and stable career.…”
Section: Discussionmentioning
confidence: 99%